A theory on reports of constructive (real) and illusory posttraumatic growth - Boerner, Michaela; Joseph, Stephen; Murphy, David (SAGE, 2017)
It has been suggested that self-reported posttraumatic growth could sometimes be considered as a way for people to protect themselves from the distress of trauma. In this case, reports of posttraumatic growth could be illusory. We suggest a theory on self-reported constructive (real) posttraumatic growth and illusory posttraumatic growth by using Rogers’s (1959) theory and the work by Vaillant (1995). Through this theoretical framework we attempt to explain when reports of posttraumatic growth are likely to be constructive and real and when such reports are likely to represent aspects of illusions. We will also consider the implications for research practice.